Metabolismo Antioxidativo para a classificação de lotes de sementes quanto ao vigor - Borba, Isabel Cristina Gouvêa de (2013)
The increased demand for high quality seeds led seed technology companies to improve their techniques aiming to associate germination and vigor with the responses of the seeds in the field. However, such responses may suffer several influences during storage and maturation process, bringing damage to the membranes' systems, leading to reactive oxygen species (ROS), which can diminish seed vigor. Thus, the antioxidative system enzymes may become an enriching alternative to classify seeds lots according to their vigor. Most works analyzing those enzymes activity report their responses related to the abiotic stress influence in different crops. In such cases, the decrease in the enzymatic activity point to seeds and seedlings with less vigor and viability. However, in this work, where the seeds were not submitted to any kind of stress, those enzymes higher activity expressed a higher ROS production, and that points to the beginning of the deterioration process, featuring lesser seeds vigor. Considering this, the work aimed to distinguish seeds lots of maize, beans and soybean through the antioxidative enzymes activity (SOD superoxide dismutase, APX ascorbate peroxidase and CAT - catalase), and relate them to viability and vigor standard test to verify if those enzymes detect differences in vigor of seeds lots. For this, the seeds of the three crops were submitted to the physiological quality standard tests, such as germination, first count and germination speed index, length and dry mass of roots and shoots, electrical conductivity and antioxidative enzymes. Through the obtained results, it was possible to verify that in beans and soybean seeds lots, which presented high heterogeneity between them, the antioxidative system enzymes activity was not efficient to separate the lots. However, in the maize seeds lots that presented high homogeneity for the physiological quality standard tests, it was possible identifying differences in the enzymes activity in the seedlings derived from those seeds lots, allowing to classify them into different vigor levels.